Embrace microservices design : know why your microservices are failing : a practical guide to revealing anti-patterns and architectural pitfalls to avoid microservices fallacies /: know why your microservices are failing : a practical guide to revealing anti-patterns and architectural pitfalls to avoid microservices fallacies. (2021) - Khan, Ovais Mehboob Ahmed; Siddiqui, Nabil; Oleson, Timothy
No abstract available